Electrostatic Assembly/Disassembly of Nanoscaled Colloidosomes for Light‐Triggered Cargo Release1. Issue 23 (27th April 2015) - Li, Song; Moosa, Basem A.; Croissant, Jonas G.; Khashab, Niveen M.
Abstract: Colloidosome capsules possess the potential for the encapsulation and release of molecular and macromolecular cargos. However, the stabilization of the colloidosome shell usually requires an additional covalent crosslinking which irreversibly seals the capsules, and greatly limits their applications in large‐cargos release. Herein we report nanoscaled colloidosomes designed by the electrostatic assembly of organosilica nanoparticles (NPs) with oppositely charged surfaces (rather than covalent bonds), arising from different contents of a bridged nitrophenylene‐alkoxysilane [NB; 3‐nitro‐ N ‐(3‐(triethoxysilyl)propyl)‐4‐(((3‐(triethoxysilyl)propyl)‐amino)methyl)benzamid] derivative in the silica. The surface charge of the positively charged NPs was reversed by light irradiation because of a photoreaction in the NB moieties, which impacted the electrostatic interactions between NPs and disassembled the colloidosome nanosystems. This design was successfully applied for the encapsulation and light‐triggered release of cargos. Abstract : Nanocapsules for large cargos : Nanoscaled colloidosomes were designed by electrostatic assembly of organosilica nanoparticles (NPs) with oppositely charged surfaces, arising from different contents of a bridged nitrophenylene–alkoxysilane derivative in the silica. The positive charge was reversed by light irradiation because of the photoreaction of nitrophenylene moieties.